2019
DOI: 10.1093/advances/nmy117
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Diets for Personal, Population, and Planetary Health

Abstract: Worldwide, the burden of morbidity and mortality from diet-related chronic diseases is increasing, driven by poor diet quality and overconsumption of calories. At the same time, the global food production system is draining our planet's resources, jeopardizing the environment and future food security. Personal, population, and planetary health are closely intertwined and will all continue to be vulnerable to these threats unless action is taken. Fortunately, shifting current global dietary patterns towards hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 51 publications
1
118
1
12
Order By: Relevance
“…There is emerging evidence to support the benefits of plant-based dietary patterns in primary prevention of CVD. Long-term epidemiologic studies have found that a healthful plant-based diet (that does not necessarily exclude all animal products) was associated with a significantly lower risk of type 2 diabetes and CVD ( 42 ). Small intervention studies have shown that a shift from a typical western diet to a vegan diet substantially lowered a atherogenic gut flora metabolite called trimethylamine-N-oxide (TMAO) which is induced by higher consumption of animal products especially red meat ( 43 ).…”
Section: Lifestyle Medicine Domain-specific Findings and Recommendatimentioning
confidence: 99%
“…There is emerging evidence to support the benefits of plant-based dietary patterns in primary prevention of CVD. Long-term epidemiologic studies have found that a healthful plant-based diet (that does not necessarily exclude all animal products) was associated with a significantly lower risk of type 2 diabetes and CVD ( 42 ). Small intervention studies have shown that a shift from a typical western diet to a vegan diet substantially lowered a atherogenic gut flora metabolite called trimethylamine-N-oxide (TMAO) which is induced by higher consumption of animal products especially red meat ( 43 ).…”
Section: Lifestyle Medicine Domain-specific Findings and Recommendatimentioning
confidence: 99%
“…One of the main factors that has influenced the popularity of soy foods is the ever-growing interest of the population toward plant-based diets and their many health benefits, together with the recognized high protein quality of soy (31,(65)(66)(67).…”
Section: Use Of Soybean and Its Derivates In Plant-based Dietsmentioning
confidence: 99%
“…The term "plant-based diets" includes many different dietary patterns that comprise higher quotas of plant products (vegetables, fruits, whole grains, legumes, nuts, and seeds) than animal ones (66). Specifically, there is evidence that soy foods may reduce low-density lipoprotein (LDL)-cholesterol levels and modestly lower blood pressure, thus reducing the risk of coronary heart disease (68).…”
Section: Plant-based Dietsmentioning
confidence: 99%
See 2 more Smart Citations